2009
DOI: 10.1242/jeb.034116
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase expression and CO2 excretion during early development in zebrafishDanio rerio

Abstract: SUMMARYCarbonic anhydrase (CA) is critical for CO 2 excretion in adult fish, but little is known of the expression or function of CA during early development. The present study examined the hypothesis that, as rates of CO 2 production increased during early development in zebrafish (Danio rerio), CA would become necessary for effective CO 2 excretion, and that the pattern of CA expression during early development would reflect this transition. Real-time RT-PCR was used to examine the mRNA expression of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…The results of a previous study (Gilmour et al, 2009) demonstrated the specificity of the zCAc knockdown and most importantly showed that zCAb was not a target for the zCAc morpholino. Thus we are confident that the similar knockdown approach used in this study also specifically targeted zCAc.…”
Section: Research Articlementioning
confidence: 91%
See 4 more Smart Citations
“…The results of a previous study (Gilmour et al, 2009) demonstrated the specificity of the zCAc knockdown and most importantly showed that zCAb was not a target for the zCAc morpholino. Thus we are confident that the similar knockdown approach used in this study also specifically targeted zCAc.…”
Section: Research Articlementioning
confidence: 91%
“…, the physiological significance of the hypercapnia-mediated tachycardia in larvae is unknown. Given that the results of a recent study (Gilmour et al, 2009) suggested that the red blood cells of larval zebrafish may be involved in CO 2 excretion, it is conceivable that internal convection might selectively promote CO 2 excretion and thereby be increased by any elevation of cardiac output associated with tachycardia. Thus the tachycardia could serve to minimize the extent of the respiratory acidosis associated with exposure to hypercapnia.…”
Section: The Cardiac Response To Hypercapniamentioning
confidence: 99%
See 3 more Smart Citations